2021
DOI: 10.4067/s0718-34022021000300059
|View full text |Cite
|
Sign up to set email alerts
|

Conflicto, territorio y extractivismo en Chile. Aportes y límites de la producción académica reciente

Abstract: El presente artículo analiza la producción académica que aborda la problemática articulada por los conceptos de conflicto, territorio y extractivismo en Chile. El análisis de 32 artículos publicados en revistas indexadas entre 2015 y 2020 da cuenta de una preocupación importante por el fenómeno. Caracterizamos esta etapa de la literatura en relación al tratamiento de los distintos conceptos, así como de los métodos utilizados, los actores estudiados y las escalas consideradas. Esta producción académica aparece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
1
0
6
Order By: Relevance
“…This study's estimation of environmental damage could help construct cost-benefit indicators or socially evaluate public or private investments that avoid environmental damage in surface waters. It could also be a crucial instrument for solving the growing conflicts among local communities, national authorities, and multinational extractive companies (Maillet et al 2021). However, it is necessary to clarify that this study has quantified only reported discharges and does not consider possible unreported or illegal discharges, which could substantially increase estimated costs.…”
Section: Discussionmentioning
confidence: 99%
“…This study's estimation of environmental damage could help construct cost-benefit indicators or socially evaluate public or private investments that avoid environmental damage in surface waters. It could also be a crucial instrument for solving the growing conflicts among local communities, national authorities, and multinational extractive companies (Maillet et al 2021). However, it is necessary to clarify that this study has quantified only reported discharges and does not consider possible unreported or illegal discharges, which could substantially increase estimated costs.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien hay trabajos, como los de Romero-Toledo (2019) y de Bolados y Babidge (2017), que explicitan con mayor detalle la posición adoptada frente a la idea de extractivismo, dicha comprensión no es profundizada en las investigaciones empíricas que llevan a cabo. Esta apreciación es compartida recientemente por Maillet et al (2021) quienes en una revisión de artículos científicos, constatan "una rutinización o inercia conceptual que suspende el cuestionamiento teórico independiente del poder comunicativo del concepto" (Maillet et al, 2021: 68) y que no realiza un mayor despliegue analítico-conceptual.…”
Section: La Polisemia En La Discusión Sobre Extractivismo En América ...unclassified
“…Ces cas sont reliés à l'expansion minière (17) pétrolière (3), gazière (3), forestière (1) et hydroélectrique ( 1) Des 25 conflits identifiés, 14 affectent des territoires autochtones « reconnus ». Au Chili, la contestation sociale s'est accrue et a éclaté massivement en octobre 2019, liant aux préoccupations sociales des questions environnementales cruciales comme la situation critique de l'eau, la dévastation forestière et les zones de sacrifice, soulevant publiquement les critiques à la multiplication des projets extractifs (Maillet et al, 2019 ;Allain, 2019 ;INDH, 2016). Berceau du modèle néolibéral (Moulián, 2002), l'État chilien soutient un système de marché 10 favorisant l'appropriation des ressources naturelles par les entreprises privées.…”
Section: De L'élaboration D'un Portrait Des Conflits Socioécologiques...unclassified